Nurturing Future of Nepal : The Impactful Role of CTVET In Technical and Vocational Education - Adhikari, Khagendra Prasad (A Bi-annual South Asian Journal of Research & Innovation, 2023)
The Council for Technical Education and Vocational Training (CTEVT) stands as an apex body in Nepali technical educational landscape, dedicated to cultivating practical skills and expertise. This article explores CTEVT historical evolution, founding principles, and its multifaceted role in enhancing technical and vocational education. The main objectives encompassing curriculum development, program accreditation, skills assessment, and industry linkage, showcasing how these functions sustain the quality and relevance of its programs. CTEVT offers a diverse range of technical and vocational programs spanning fields such as engineering, health, agriculture, hospitality and hotel management. These programs equip students with practical skills aligned with job market demands, preparing them for meaningful contributions to the workforce. A fundamental focus is its collaborative engagement with industries and employers through industry advisory boards, curriculum updates, internships, and industry visits. CTEVT ensures that its programs remain attuned to current trends, market demands and enhancing graduates’ employability. The article underscores its vital initiatives in rural and underserved areas. These efforts empower marginalized groups through accessible education and income-generating skills, catalyzing economic growth and sustainable development within communities. CTEVT emerges as a hub in workforce development, economic growth and skill enhancement. Its proactive approach to curriculum innovation, industry integration and equitable education highlights its commitment to nurturing a capable and empowered workforce thereby contributing to societal advancement.